2011
DOI: 10.1177/206622031100300203
|View full text |Cite
|
Sign up to set email alerts
|

Desisting in France: What Probation Officers Know and Do. A First Approach

Abstract: French probation services operate without much knowledge of criminological literature. Thus they have never heard of desistance. This research aimed at verifying whether they nonetheless had an overall idea of what it takes to desist and whether they helped offenders with obstacles to desistance. Their opinions were contrasted to those of other practitioners and the views of desisters. Despite the methodological limitations of this small scale study, one can nonetheless attempt to formulate a few conclusions: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Some research studies have examined (in passing) what the experience of desistance is like for those who are less ‘successful’ than Maruna’s and Aresti’s interviewees, but who still seem to be managing to stay away from crime. In French research, most desisters were found to live a ‘normal’ life, concentrating on themselves and their families, rather than trying to contribute to society at large (Herzog-Evans, 2011). Healy (2010) also found little evidence of generativity in a sample of desisters.…”
Section: Introductionmentioning
confidence: 99%
“…Some research studies have examined (in passing) what the experience of desistance is like for those who are less ‘successful’ than Maruna’s and Aresti’s interviewees, but who still seem to be managing to stay away from crime. In French research, most desisters were found to live a ‘normal’ life, concentrating on themselves and their families, rather than trying to contribute to society at large (Herzog-Evans, 2011). Healy (2010) also found little evidence of generativity in a sample of desisters.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly the message that most of these young authors convey is that social work is now becoming a thing of the past in France (Dindo, 2011; de Larminat, 2012; Rintaud, 2008). A study into the practices of supporting desistance amongst French POs and what desisters thought about them sadly confirmed that actively supporting desistance or addressing offenders’ needs was, in general, not part and parcel of French probation work (Herzog-Evans, 2011b). It was clear from the POs’ discourse that a lot of them had lost touch with their original social work ethos and identity (Perrier, 2013) and that this identity was now shifting towards, on the one hand, a rather distant and more often than not loose control, and, on the other hand, judicial clerk-like work consisting in the preparation of decisions for and acting as a go-between with the JAP and community agencies and resources (Herzog-Evans, 2013 b).…”
Section: The Researchmentioning
confidence: 99%
“…Associations are also involved in services that probation services do not take on, either by choice or culture (Herzog-Evans, 2011b), such as working with families, victims, addiction, health, education or vocational training. Importantly, associations are increasingly in charge of social work, which probation services have essentially abandoned in the recent years.…”
Section: Third Sector and Probation Services: ‘Leftovers’ And Competitionmentioning
confidence: 99%
“…Their message is a positive one and it made me reflect on previous research I had conducted on desistance à la française (Herzog‐Evans ) where French probation officers told me almost word for word, the same thing: their major role was to plant seeds which they hoped might later flourish. At the time, I analysed this as particularly revealing of their lack of ambition and their abstaining, and unsupportive supervision.…”
mentioning
confidence: 90%